BEAUTY IN THE DIGITAL AGE: WHAT INFLUENCES WOMEN TO BUY SKINCARE ONLINE? - Wei , Harn Foo; Mat Hasan, Nor Hasliza; Ibrahim, Nor Fauziana (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
As e-commerce continues to grow, understanding consumer behavior in the online skincare market becomes increasingly important. This research examines the key factors influencing women’s intention to purchase skincare products online. It examines the relationship between Product Price (PP), Brand Trust (BT), Perceived Usefulness (PU), Review Credibility (RC), and word of mouth (WOM) with purchase intention among women. Using a quantitative approach, this study aims to gather and analyze data from Malaysian women to assess the impact of these factors on their intention to purchase skincare products online. Data is collected through a questionnaire distributed via email, with a sample size of 395 respondents. The study utilizes reliability analysis, multiple regression analysis, and Pearson's correlation analysis for data analysis. Evidence from the study shows that brand trust and word-of-mouth significantly impact purchase intention, whereas product price, perceived usefulness, and review credibility show no significant effect. The study intends to explore consumer behavior trends among female shoppers in Malaysia's digital skincare industry, in particular the online skincare market among women. These insights could inform e-commerce strategies for skincare companies and help businesses enhance brand credibility and leverage word-of-mouth marketing. It will ultimately contribute to the development and improvement of the online skincare retail sector in Malaysia.